Piloting a Diagnostic Foot and Ankle Fracture Sonographic Algorithm with Rural and Adolescent Patients - Tomas Alamin; Margaret Lin-Martore; Aaron Kornblith; Aidan O'Donnell; Sally Graglia (CINQUILL Medical Publishers Inc., 2024)
Background: Foot and ankle injuries are a common presenting complaint to the Emergency Department (ED) and are often assessed with plain radiography. Rural environments may not have access to radiography mandating the referral or transfer patients to regional centers for definitive diagnosis. The Ottawa Foot and Ankle Rules (OFAR) is a clinical decision rule that can assist in ruling out fractures. Point of care ultrasound (POCUS) can augment this decision rule. The objective of this study was to assess both the feasibility and test characteristics of a previously described POCUS augmented clinical assessment, OFAR-POCUS, for adolescent and adult patients with foot and ankle pain in a rural environment. Methods: This was a prospective cohort study from June to August 2022 including patients with chief complaint of foot or ankle injury presenting to a rural clinic. Patients were included if they had positive finding(s) on the OFAR Test and required radiographic imaging. Patients were excluded if they did not consent, speak English, were unable to be scanned, had obvious joint deformities, had altered mental status, were not physiologically stable, had other injuries preventing sonography, were pregnant, or had previous injury with internal fixation, osteomyelitis, or rheumatoid arthritis. POCUS was performed before transport for radiography. POCUS examiners were POCUS novices who underwent a one and a half to two-hour, standardized foot and ankle POCUS training session. All POCUS studies were reviewed by two emergency medicine ultrasound fellowship trained faculty for quality assurance. Standard test characteristics were calculated for bedside clinician and expert POCUS interpretations compared to the radiographic control. Results: Thirteen POCUS examiners performed exams on 20 patients included in analysis; four patients had fractures on radiograph (20%). The bedside clinician POCUS interpretation had sensitivity (SN) = 100% (95% Cl, 40%-100%), specificity (SP) =94% (95% Cl, 70%-100%), and negative likelihood ratio (-LR) = 16.00 (95% Cl, 2.40-106.73). Expert POCUS interpretation had SN=75% (95% Cl, 19%-99%), SP=75% (95% Cl, 48%-93%), and -LR=0.33 (95% Cl, 0.06-1.86). Conclusion: A POCUS enhanced clinical strategy for clinically significant foot and ankle fractures in adolescent and adult patients in a rural setting is feasible. Larger studies are required to further characterize test characteristics and use of foot and ankle POCUS where plain radiography is unavailable.